Atrial fibrillation impairs ventricular function by altering excitation-contraction coupling in the human heart. (25th November 2020) - Pabel, S; Knierim, M; Alebrand, F; Paulus, M; Herting, J; Hollemann, D; Sedej, S; Von Lewinski, D; Fischer, T; Schmid, C; Hasenfuss, G; Brochhausen, C; et al.
Abstract: : Atrial fibrillation (AF) often co-exists in patients with heart failure (HF). Recent clinical evidence suggests that the arrhythmic component of AF alone may contribute to ventricular dysfunction. However, the pathophysiological effects of a non-tachycardic AF on the human ventricle are unknown. To investigate the effects of normofrequent AF on the human ventricle we investigated ventricular myocardium from patients with preserved ejection fraction with sinus rhythm (SR) or AF in the absence of HF (compensated hypertrophy, EF>50%, matched clinical characteristics). In histological analysis we detected no difference between SR (n=9) vs. AF (n=6) regarding the amount and distribution of fibrosis. For functional investigation, Ca-handling was studied (Fura-2 AM). While systolic Ca-transient amplitude was in trend reduced in isolated human ventricular AF cardiomyocytes, we found a significantly prolonged Ca-elimination time (n=17–22 cells/4 pat.). Using caffeine application, a decreased SR Ca-load in AF was detected, which may be explained by a significant decrease in SERCA2a activity (ksys-kCaff, n=10–12/4 pat.). Patch-clamp experiments revealed a prolonged action potential duration in AF cardiomyocytes (n=5/15 cells). For the standardized evaluation of the mechanisms of persistent normofrequent arrhythmia, we simulated AF in vitro by using arrhythmic (1 Hz, 40% R-R-variability) or rhythmic (1 Hz) field stimulation. We performed contractility experiments using in-toto isolated human ventricular trabeculae from explanted human hearts. After 8h of pacing, arrhythmically stimulated human trabeculae showed a significantly reduced systolic force, an increase in diastolic tension and a prolonged relaxation (n=11–12 trabeculae/11 pat.). For studying the cellular effects of persistent normofrequent arrhythmia in a model suitable for chronic pacing (up to 7 days), we utilized human iPSC cardiomyocytes (iPSC-CM) from healthy donors (n=6). After 7 days, arrhythmic paced iPSC-CM showed a significantly reduced systolic Ca-transient amplitude, a prolonged Ca-elimination time (n=35/45 cells) as well as a reduced SR Ca-load and a trend towards a lower SERCA2a activity compared to control (n=11 cells). Confocal line-scans (Fluo-4 AM) showed an increased diastolic SR Ca-release, which might also explain the reduced SR Ca-content (n=45/35 cells). Moreover, in irregularly paced iPSC-CM we found significant increased levels of cytosolic Na (n=69 cells each) and in patch-clamp experiments a significantly prolonged action potential duration (n=14/11 cells/3 diff.). This study demonstrates that a normofrequent arrhythmic ventricular excitation as it occurs in AF impairs human ventricular myocardial function by altering cardiomyocyte excitation-contraction coupling. Thus, this study provides the first translational mechanistic characterization and the potential negative impact of isolated AF in the absence of tachycardia on the human ventricle. Funding Acknowledgement: Type of funding source: None